BS EN 17388-2. Flexible sheets for waterproofing. Environmental product declarations. Product Category Rules for reinforced bitumen, plastic and rubber flexible sheets for roof waterproofing. Part 2. Cradle to gate with options, modules C1-C4 and module D (22nd January 2021) - British Standards Institution,
No abstract available